God vs. Darwin the war between evolution and creationism in the classroom - Singham, Mano. (Lanham, Md. : Rowan & Littlefield Education, 2009)
"In God vs. Darwin, Mano Singham dissects the legal battle between evolution and creationism in the classroom beginning with the Scopes Monkey trial in 1925 and ending with an intelligent design trial in Dover, Pennsylvania, in 2005. A publicity stunt, the Scopes Monkey trial had less to do with legal precedence than with generating tourism dollars for a rural Tennessee town. But the trial did successfully spark a debate that has lasted more than 80 years and simply will not be quelled despite a succession of seemingly definitive court decisions. In the greatest demonstration of survival, opposition to the teaching of evolution has itself evolved. Attempts to completely eliminate the teaching of evolution from public schools have given way to the recognition that evolution is here to stay, that explicitly religious ideas will never be allowed in public schools, and that the best that can be hoped for is to chip away at the credibility of the theory of evolution." "Dr. Singham answers complex questions: Why is there such intense antagonism to the teaching of evolution in the United States? What have the courts said about the various attempts to oppose it? Sprinkled with interesting tidbits about Charles Darwin and the major players of the evolution vs. creationism debate, readers will find that God vs. Darwin is charming in its embrace of the strong passions aroused from the topic of teaching evolution in schools."--BOOK JACKET.
Introduction -- The history behind Inherit the wind -- The rising religious opposition to Darwin -- The free speech train -- The Scopes pre-game show -- The Scopes trial -- The Scopes appeal -- The history of religion in U.S. public schools -- Religion and the establishment clause after Scopes -- Evolution back in the courts -- Adam and Eve and evolution -- The rise and fall of "creation science" -- Creation science born again as intelligent design -- Why some hate evolution: the wedge document revelations -- The endorsement test and the "informed, reasonable observer" -- The Dover policy on teaching evolution -- The Dover verdict -- The aftershocks of Dover -- What next? -- The long view.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Evolution (Biology) -- Religious aspects -- Christianity; Human evolution -- Religious aspects -- Christianity; Scopes, John Thomas -- Trials, litigation, etc; Evolution (Biology) -- Study and teaching -- Law and legislation -- Tennessee; Evolution (Biology) -- Study and teaching (Secondary) -- Pennsylvania -- Dover (Township); Creationism -- Study and teaching (Secondary) -- Pennsylvania -- Dover (Township); Intelligent design (Teleology) -- Study and teaching (Secondary) -- Pennsylvania -- Dover (Township); Electronic books